A Faster Third-Order Masking of Lookup Tables - Anju Alexander; Annapurna Valiveti; Srinivas Vivek (Transactions on Cryptographic Hardware and Embedded Systems, 2022)
Masking of S-boxes using lookup tables is an effective countermeasure to thwart side-channel attacks on block ciphers implemented in software. At first and second orders, the Table-based Masking (TBM) schemes can be very efficient and even faster than circuit-based masking schemes. Ever since the customised second-order TBM schemes were proposed, the focus has been on designing and optimising Higher-Order Table-based Masking (HO-TBM) schemes that facilitate masking at arbitrary order. One of the reasons for this trend is that at large orders HO-TBM schemes are significantly slower and consume a prohibitive amount of RAM memory compared to circuit-based masking schemes such as bit-sliced masking, and hence efforts were targeted in this direction. However, a recent work due to Valiveti and Vivek (TCHES 2021) has demonstrated that the HO-TBM scheme of Coron et al. (TCHES 2018) is feasible to be implemented on memory-constrained devices with pre-processing capability and a competitive online execution time. Yet, currently, there are no customised designs for third-order TBM that are more efficient than instantiating a HO-TBM scheme at third order. In this work, we propose a third-order TBM scheme for arbitrary S-boxes that is secure in the probing model and under compositions, i.e., 3-SNI secure. It is very efficient in terms of the overall running time, compared to the third-order instantiations of state-of-the-art HO-TBM schemes. It also supports the pre-processing functionality. For example, the overall running time of a single execution of the third-order masked AES-128 on a 32-bit ARM-Cortex M4 micro-controller is reduced by about 80% without any overhead on the online execution time. This implies that the online execution time of the proposed scheme is approximately eight times faster than the bit-sliced masked implementation at third order, and it is comparable to the recent scheme of Wang et al. (TCHES 2022) that makes use of reuse of shares. We also present the implementation results for the third-order masked PRESENT cipher. Our work suggests that there is a significant scope for tuning the performance of HO-TBM schemes at lower orders.